Pengaruh Waktu Penutupan Katup Terhadap Tekanan Transient Pada Pipa ( Tinjauan Numerik Dan Eksperimen ) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This reseach was intended to find the effects of various closure times of valve on pressure oscillation in a straight pipe. Mathematical model which was relevan to this case was solved using the characteristic method and Brunone friction model improved by Vitkovsky as an unsteady friction model. Diamond grid was applied to setting up the method of characteristic scheme. The solusion of the mathematical model was verified for various closure times of valve. The result compared quite well with the experiment. It was shown that the pressure pattern was in good aggrement. Various valve's closure time up to critical closure time was attainned to significant diference of pressure rise, This was due to various temporal deceleration of flow effect of the increasing resistant of valve. Pattern of increasing resistant of valve followed dimensionless characteristic of valve.